Determinação da vida útil de pernil suíno sem osso resfriado - Messias, Camila Ramos (2023)
Pork has a wide national and international consumer market, so its shelf life must be known by its manufacturers. The aim of this study was to assess the stability of chilled boneless pork shank, with approximately 10% fat, sold by a slaughterhouse registered with the Ministry of Agriculture and Livestock SIF/DIPOA, stored under refrigeration at 0.0 ± 2.0 °C. Samples of boneless pork shank were stored in the cooling chamber of an industry located in the western region of Paraná at 0.0 ± 2.0 °C and evaluated from 2 days (48 hours after slaughter) to 27 days. To assess the stability of the samples during storage, microbiological, physicochemical and sensory analyses were carried out. The microbiological analyses carried out were Salmonella spp., Escherichia coli and mesophilic aerobes. Physico-chemical analyses included composition and instrumental analyses (protein, lipid, ash and moisture content, pH, water activity, and instrumental color) and oxidative stability (Kreiss analysis, TBARs, percentage of metmyoglobin formation, and peroxide index). The sensory stability of the sample was assessed using the difference from the control test with 21 previously selected and trained tasters. The microbiological results are in accordance with current legislation; the results for mesophilic aerobes were analyzed using the Gompertz model, the physicochemical and sensory analyses were subjected to analysis of variance (ANOVA), and the means were compared using the Tukey and Dunnett tests, respectively, with a 95% confidence level. The results of the physicochemical analyses indicated that the chilled boneless pork shank meat remained in compliance in terms of product composition during the period analyzed. The results of the microbiological analysis showed values within the limits established by current legislation in Brazil. The Gompertz predictive model efficiently represented the behavior of mesophilic aerobes counts as a function of storage time, with a growth rate of 0.0384 log UFC/g per hour and a maximum mesophilic aerobes population of 3.1 log UFC/g. During the storage period, the peroxide index was < 0.5 mEq/kg of the sample, negative for the Kreiss qualitative analysis, metmyoglobin index < 72.31%, and < 0.44 mg of malonaldehyde/kg of the sample, indicating adequate stability under the storage conditions tested. However, the sensory analysis allowed us to observe that the color and odor of the samples showed noticeable changes from the 16th day of storage, and on the 24th and 27th days of storage, there was greater rejection among the tasters, and therefore, limiting the storage period in a cold room at an average temperature of -0.46 ± 1.33 °C until the 21st day of storage.